Desain Pengembangan Laboratorium Terintegrasi dan Berkelanjutan Perguruan Tinggi Keagamaan Islam Negeri - Aprizal Ahmad; Zulpadrianto Zulpadrianto; Nini Nini; Yeni Etma Nazar (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
Laboratories play a pivotal role in supporting teaching, research, and community engagement in higher education. However, laboratory governance in Indonesian State Islamic Higher Education Institutions remains fragmented due to inconsistent quality assurance practices, limited integration of laboratory functions with research, and shortages of qualified technical personnel. Existing laboratory management frameworks, including the Laboratory Quality Management System (LQMS), ISO 9001, and ISO/IEC 17025, primarily emphasize technical compliance while offering limited guidance on integrating institutional quality assurance with the distinctive values of Islamic higher education. This study develops an integrated and sustainable laboratory governance model by synthesizing the Internal Quality Assurance System (IQAS), international quality standards, and Islamic ethical principles. Employing a qualitative research and development design with a multiple-case study approach, the study collected data from 110 participants across three Indonesian State Islamic Higher Education Institutions through semi-structured interviews, observations, document analysis, and user satisfaction assessments. Data were analyzed using inductive thematic analysis, cross-case synthesis, and methodological triangulation. The findings reveal two dominant governance configurations—integrated laboratories and study program-based laboratories—each with complementary strengths but facing common challenges in technical staffing, research utilization, and continuous quality improvement. Based on these findings, the study proposes the Integrated Sustainable Laboratory Governance Model (ISLGM), integrating the 12 Quality System Essentials, IQAS, ISO 9001, ISO/IEC 17025, and Islamic values into a unified governance framework. The model advances laboratory governance theory by contextualizing quality management within Islamic higher education and provides an evidence-based framework for strengthening laboratory quality, research productivity, institutional resilience, and sustainable governance.